ASSOCIATIONS OF BLOOD GROUPS ANTIGENS OF AB0 AND RHESUS SYSTEMS WITH THE DEVELOPMENT OF CHRONIC KIDNEY DISEASE, GLOMERULONEPHRITIS - V. Kaminskyy (Український Журнал Нефрології та Діалізу, 2014)
Introduction. Finding of biological markers of genetic predisposition to the formation of glomerulonephritis (GN) will promote prediction the probability of its development still at an early stage and provide the growth of preventive direction of medicine. The purpose of the study is to evaluate the risk of GN development by antigens of AB0 and rhesus (Rh) blood groups.